Lost to the collective : suicide and the promise of Soviet socialism, 1921-1929 - Pinnow, Kenneth Martin (Ithaca : Cornell University Press, 2010)
Arguing that the Soviet regime represented a particular response to the pressures & challenges of modernity, this book examines Soviet socialism, from its intense concern with the individual to its quest to build an integrated society, as one response to the larger question of human unity.
Suicide and social (dis)integration in revolutionary Russia -- Suicide and the collective individual in the Bolshevik Party -- Suicide and social autopsy -- Markers of modernity : moral statistics and the making of Soviet suicide -- Suicide and surveillance : medicopolitics in the Red Army -- Epilogue : suicide and Stalinism.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Suicide -- Soviet Union -- History; Suicide -- Political aspects -- Soviet Union; Soviet Union -- Social conditions -- 1917-1945.; Suicide -- URSS -- Histoire; Suicide -- Aspect politique -- URSS; URSS -- Conditions sociales -- 1917-1945.; HISTORY -- Europe -- Russia & the Former Soviet Union; Social conditions; Suicide; Soviet Union; Gesellschaft; Suizid; Sowjetunion; représentation sociale -- suicide -- URSS -- 1921 -- 1929.; 1917 - 1945; History